2021
DOI: 10.2147/ijn.s335757
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed Molecular Imaging Strategy Integrated with RNA Sequencing in the Assessment of the Therapeutic Effect of Wharton’s Jelly Mesenchymal Stem Cell-Derived Extracellular Vesicles for Osteoporosis

Abstract: Introduction:Osteoporosis is a result of an imbalance in bone remodeling. Mesenchymal stem cell-derived extracellular vesicles (MSC-EVs) have been considered as a potentially promising treatment for osteoporosis. However, the therapeutic effect, genetic alterations, and in vivo behavior of exogenous EVs for osteoporosis in mice models remain poorly understood. Methods: A multiplexed molecular imaging strategy was constructed by micro-positron emission tomography (µPET)/computed tomography (CT), µCT, and optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 69 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have found that the PI3K/Akt signaling pathway plays an important role in bone formation by regulating the potential and direction of early BMSC differentiation [ 107 ]. Lu et al [ 108 ] analyzed the changes in mRNA expression profiles in bone tissue of OVX mice treated with or without MSC-EVs by the next-generation sequencing (NGS) technique to identify the key intrinsic cargoes and the key signaling pathways involved in the treatment of OP with MSC-EVs. This study found that MSC-EVs may exert their therapeutic effects on OP by upregulating extracellular matrix-associated gene expression and activating the PI3K/Akt signaling pathway through the intrinsic miRNAs, including miR-21, miR-29, and miR-221.…”
Section: Mechanisms Of Msc-evs In Opmentioning
confidence: 99%
“…Previous studies have found that the PI3K/Akt signaling pathway plays an important role in bone formation by regulating the potential and direction of early BMSC differentiation [ 107 ]. Lu et al [ 108 ] analyzed the changes in mRNA expression profiles in bone tissue of OVX mice treated with or without MSC-EVs by the next-generation sequencing (NGS) technique to identify the key intrinsic cargoes and the key signaling pathways involved in the treatment of OP with MSC-EVs. This study found that MSC-EVs may exert their therapeutic effects on OP by upregulating extracellular matrix-associated gene expression and activating the PI3K/Akt signaling pathway through the intrinsic miRNAs, including miR-21, miR-29, and miR-221.…”
Section: Mechanisms Of Msc-evs In Opmentioning
confidence: 99%